Experimental estimation and CFD validation of an Electro Submersible Pump's (ESP) curve for two fluids with different viscosities (2018)
"Propper function of electrical submersible pumps (ESP) are crucial to oil field operations, given that the cost of any intervention needed to treat any flaw with the ESP could surpass the initial cost of the equipment. This study addresses pump degradation caused by fluid viscosity, analyzing a numerical method (CFD) and a more common graphical method as an approach to predict pump degradation. The behavior of flow inside a 4-stage radial flow ESP is simulated evaluating two different fluids (water and mineral oil). The realizable k-? All wall y+ model is used to estimate results in turbulent flow, obtaining satisfactory accuracy when estimating the head curve of the 4-stage ESP. Through a velocity profile of the flow inside the impeller, recirculating flow is observed. Using the CFD analysis is found to be a better approximation to estimate head curve degradation, rather than the empirical method."--Tomado del Formato de Documento de Grado.